Peer support and healthy lifestyle among adolescents in urban areas in Indonesia - Rachmawati, Praba Diyan; Krisnana, Ilya; Kurnia, Iqlima Dwi; Quraniati, Nuzul; Arief, Yuni Sufyanti; Danasari, Titis Mustikowati; Rithpo, Pratuma (Intelektual Pustaka Media Utama, 2024)
Unhealthy lifestyles among adolescents in urban areas are still a problem. Peers are role models in adolescent's lifestyle. However, little is known about the peer support in eating behavior, sedentary lifestyle and physical activities, which thus needs to be explored. This study aims to analyze the relationship between peer support and adolescent lifestyle. This study used a cross-sectional design with a sample size of 105 adolescents using proportional stratified random sampling. Data were collected by questionnaire. The Spearman rho test was performed to identify the relationship between peer support within a sedentary lifestyle and eating behavior, while to identify the relationship between peer support and physical activity using pearson, the level of significance was determined as p≤0.05. The results showed that there was a relationship between peer support and eating behavior (p=0.012; r=0.243) as well as adolescents' physical activity (p=0.001; r=0.324). There is no relationship between peer support and a sedentary lifestyle both on weekdays (p=0.181; r=0.131) and on weekends (p=0.735; r=0.033). The results show that peers have an important role in improving healthy lifestyle patterns in adolescents, especially in eating behavior and physical activity, so peer involvement interventions to improve healthy lifestyles in adolescents are recommended.